Africanidade - Oliveira, Ediney nunes de; Novais, Cleide Farias; Franco, Aracelly de Oliveira; Correia, Marineuza Lopes; Silva, Rosangela gomes da; Barros, Cleber Miranda; Paula, João Batista de; Lima, Eliene Xavier de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf